Magnetic and electrical properties of H13 tool steel by bound metal deposition 3D printing: Annealed and non-annealed - Minh, Le Hoang Trong; Duyen, Do Qui; Vinh, Ngo Chi; Hung, Nguyen Quoc; Trinh, Le Vu Phuong (Vietnam Journal of Mechanics, 2025)
In recent years, a new additive manufacturing process called bound metal deposition has emerged and advanced dramatically. While most studies have concentrated mainly on the mechanical properties of 17-4PH stainless steel, with some focus on tool steels, there remains a gap in studies exploring a wider variety of materials and other applications. This study aims to address this by using another type of steel, namely H13 tool steel. The material is employed to form 3D-printed samples through the bound metal deposition process. Material characterizations of magnetic and electrical properties are subsequently performed on the printed samples. In addition, the impact of a thermal annealing post-process is studied to better understand its effects on the material properties. Underlying mechanisms responsible for changes in material properties are proposed to provide valuable insights into different treatments that influence the behavior of the investigated materials. Additional samples of conventional hot-rolled SKD61 tool steel will also be measured and compared with the 3D-printed samples. The findings of this research significantly expand the potential applications of 3D-printed steel materials, particularly in fields that rely on magnetic and electrical characteristics. By exploring a broader range of steels and processing techniques, this study enhances understanding of the capabilities of additive manufacturing in producing materials with diverse functional properties.